Nationalism Education in the 21st Century: A Study of Civic Instruction Among Indonesian Youth - Zulfaida, Arini; Arifin, Muhammad; Supriadi; Misyanto (International Journal of Sustainable English Language, Education, and Science, 2025)
This study aims to describe how nationalism education is applied to the young generation of Indonesia amid the challenges of the globalisation era. The approach used in this research is descriptive qualitative and was conducted in a number of senior high schools. Data collection techniques included interviews, observations, and documentation studies. The research subjects consisted of teachers of Pancasila and Civics Education (PPKn) subjects and students who attended PPKn classes in East Java Province. Data were analysed using the inductive analysis method. The research findings identified two main forms of nationalism education for the younger generation in the era of globalisation, namely through the internalisation of national values in Civic Education learning and the implementation of extracurricular activities. Teachers integrate national values in the learning process by developing teaching strategies, materials, media, and student worksheets that are full of nationalism content. Meanwhile, extracurricular activities at school are also a means of instilling national values to students.